Exploring a novel panel-core connection method of large size lattice sandwich structure based on wire arc additive manufacturing - Tianqiu Xu (Elsevier, 2021)
Large size sandwich structure is involved in a wide range of applications, such as aerospace and ship. However, the weak connection between panel and lattice is the bottleneck problem restricting their application. To solve this problem, this work demonstrates a novel circular scanning connection method based on pulse hot-wire arc additive manufacturing (PHWAAM) to connect the centimeter-scale and meter-scale panel. This method exhibits great connection quality (without unmelted holes) and high efficiency (about 60 s for each connection). The optimized process is studied, based on systematical analysis of the microstructure, the macro defects, and the compression testing results. By comparing and analyzing three different connection modes, the optimized circular scanning process has the advantages of low heat input and high deposition efficiency. It can be observed from the microstructure that there are equiaxed crystals and short columnar crystals in the connection area. The width of acicular α phase is finer than that of other processes, which is conducive to improving the mechanical properties. The connection area of the circular scanning process has a better matching of strength and plasticity through the compression test. Finally, the proposed connection method is also applicable to fabricate multi-cell lattice sandwich structure.